N1‐Methylnicotinamide as Biomarker for MATE‐Mediated Renal Drug–Drug Interactions: Impact of Cimetidine, Rifampin, Verapamil, and Probenecid. Issue 5 (12th February 2023) - Müller, Fabian; Hohl, Kathrin; Keller, Sascha; Schmidt‐Gerets, Sven; Deutsch, Birgit; Schuler‐Metz, Annette; Fromm, Martin F.; Stopfer, Peter; Gessner, Arne
Abstract : N 1 ‐methylnicotinamide (NMN) has been proposed as endogenous biomarker for drug–drug interactions mediated by inhibition of multidrug and toxin extrusion proteins (MATEs) at the renal proximal tubule. We analyzed NMN in plasma and urine samples of two clinical trials investigating a new probe drug cocktail (consisting of digoxin, metformin, furosemide, and rosuvastatin) dedicated to clinically relevant drug transporters. In trial 1, NMN was investigated after single‐dose treatment with individual cocktail components or after cocktail treatment. In trial 2, NMN was investigated after treatment with cocktail alone or with cocktail + inhibitor (cimetidine, a MATE inhibitor; or rifampin, verapamil, or probenecid, inhibitors of other transporters). In trial 1, NMN kinetics in plasma and urine were essentially not affected by individual cocktail components or after cocktail treatment. In trial 2, NMN renal clearance from 0 to 12 hours (CLR, 0–12 ) geometric mean ratio (GMR) after cocktail + cimetidine vs. cocktail alone was 75% (90% confidence interval (CI): 65–87%). NMN CLR GMR after cocktail + verapamil, + rifampin, or + probenecid vs. cocktail alone was 99% (90% CI: 81–121%), 91% (90% CI: 75–111%), and 107% (90% CI: 91–126%), respectively. Compared with creatinine CLR and creatinine area under the plasma‐concentration time curve, NMN CLR was more specific and more sensitive for renal MATE inhibition. Absence of impact of the cocktail on NMN in trial 1 allows for utilization of NMN in studies using this transporter cocktail. Trial 2 data support that NMN CLR is a specific and sensitive marker for MATE‐mediated renal drug–drug interactions.